2020
DOI: 10.1007/s11239-020-02323-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining lung ultrasound and Wells score for diagnosing pulmonary embolism in critically ill COVID-19 patients

Abstract: Subpleural consolidations have been found in lung ultrasound in patients with COVID-19, possibly deriving from pulmonary embolism (PE). The diagnostic utility of impact of lung ultrasound in critical-ill patients with COVID-19 for PE diagnostics however is unclear. We retrospectively evaluated all SARS-CoV2-associated ARDS patients admitted to our ICU between March 8th and May 31th 2020. They were enrolled in this study, when a lung ultrasound and a computed tomography pulmonary angiography (CTPA) were documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
(34 reference statements)
1
26
0
Order By: Relevance
“…Studies on the use of clinical probability scoring in COVID-19 patients is thus far very limited. One study indicated a Wells score > 2 had a higher correlation for VTE on imaging in critically ill COVID-19 patients[ 18 ]. Despite the limited evidence, use of a clinical prediction scoring tool should be considered in conjunction with clinical judgement when defining pretest probability of VTE in COVID-19 patients.…”
Section: What Is the Role Of Clinical Probability Scores In Directingmentioning
confidence: 99%
“…Studies on the use of clinical probability scoring in COVID-19 patients is thus far very limited. One study indicated a Wells score > 2 had a higher correlation for VTE on imaging in critically ill COVID-19 patients[ 18 ]. Despite the limited evidence, use of a clinical prediction scoring tool should be considered in conjunction with clinical judgement when defining pretest probability of VTE in COVID-19 patients.…”
Section: What Is the Role Of Clinical Probability Scores In Directingmentioning
confidence: 99%
“…Although LUS is not currently considered in the main international guidelines for COVID-19 patient management, some authors have proposed semi-quantitative LUS scores for COVID-19 pneumonia, which can be used to quantify lung aeration [ 55 , 61 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. The most widely used is called the lung ultrasound score (LUSS) [ 61 ], global or total LUS score [ 89 , 91 ], or global LUS aeration score [ 93 ], in which 0–3 points are assigned for each of the 12 zones according to ultrasound features [ 84 , 85 , 86 , 87 , 89 , 90 ]: 0 = normal; 1 = well-defined B lines (B1); 2 = coalescent B lines or white lung (B2); and 3 = consolidation ( Figure 5 ).…”
Section: Lung Ultrasoundmentioning
confidence: 99%
“…Peschel et al [ 93 ] used 0 to 4 points for up to 12 zones; this score, called the lung aeration score (LAS), is assessed by calculating the arithmetic mean of the points of all examined areas. Recently, Zotzmann et al [ 92 ] advocated a combination of LUS and the Wells score as a screening tool for pulmonary embolism (PE) in COVID-19 ARDS. The baseline LUS score (within 24 h of admission) would be roughly linked to the eventual need for invasive mechanical ventilation and would be a strong predictor of mortality [ 91 ].…”
Section: Lung Ultrasoundmentioning
confidence: 99%
“…It has been explained how pulmonary thrombosis and arterial and venous thromboembolism affecting a sizeable proportion of patients in ICU, could cause DVT, PE, ischaemic stroke, myocardial infarction and systemic arterial embolism [153]. Zotzmann et al [154] retrospectively evaluated all SARS-CoV2-associated ARDS patients admitted to ICU who underwent lung ultrasound and a computed tomography pulmonary angiography (CTPA) that was considered the gold standard for the detection of PE. In addition, Wells score was calculated to estimate the probability of PE.…”
Section: Imaging In Icu Patientsmentioning
confidence: 99%
“…In combination with a Wells score >2, this may indicate a high-risk for PE in COVID-19. [154] Accumulating evidence suggests that despite the use of anticoagulant therapy, there is a high incidence of thromboembolism events leading to the hyperinflammatory state especially in ICU patients [131]. Worth noticing, the majority of patients admitted to the ICU who requires infusion of vasoactive agents or haemodialysis receives a central venous catheter (CVC) that often produces catheter-related thrombosis (CRT).…”
Section: Imaging In Icu Patientsmentioning
confidence: 99%